Electroconvulsive therapy and anticoagulation after pulmonary embolism: a case report - Lazaro,Julio Cesar (2014)
Introduction Electroconvulsive therapy (ECT) is considered the most effective treatment for catatonia regardless its underlying condition. The rigid fixed posture and immobility observed in catatonia may lead to several clinical complications, of which, pulmonary embolism (PE) is one of the most severe. The rapid improvement of the psychiatric condition in catatonia-related PE is essential, since immobility favors the occurrence of new thromboembolic events and further complications. In that scenario, ECT should be considered, based on a risk-benefit analysis, aiming at the faster resolution of the catatonia. Methods Case report and literature review. Results A 66-years-old woman admitted to the psychiatric ward with catatonia due to a depressive episode presented bilateral PE. Clinically stable, but still severely depressed after a trial of antidepressants, she was treated with ECT in the course of full anticoagulation with enoxaparin. After five ECT sessions, her mood was significantly better and she was walking and eating spontaneously. She did not present complications related either to PE or to anticoagulation. After the eighth ECT session, she evolved with hypomania, which was managed with oral medication adjustments. The patient was completely euthymic at discharge. Conclusion The case we presented provides further evidence to the anecdotal case reports on the safety of ECT in the course of concomitant full anticoagulant therapy after PE, and illustrates how, with the proper precautions, the benefits of ECT in such condition might outweigh its risks.